In Anita Desai's Novels, Existential Perspective: Exploring Existential Themes in Anita Desai's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Existentialism is a contemporary philosophical philosophy that deals with man's disillusionment and sorrow. It was more on attitude to life, a vision, or what Kaufman calls a timeless sensibility that may be distinguished here and there is the past, and it originated in the philosophical and literary writings of Jean Paur Sartre. Existentialism began as a philosophical idealism that grew into a forceful uprising against reason, rationality, positivism, and the customary ways in which early thinkers represented man across time. Man's autonomy, assertion of his subjective self, defiance of reason and logic, denial of conventional values, institutions, and philosophy, and his sense of life's absurdity and nothingness are some of the existential themes represented in the writings of existentialism's proponents.